KETAHANAN PANGAN RUMAH TANGGA DI JAWA BARAT: ANALISIS DATA SUSENAS 2012 - Heryanah Heryanah (Populasi, 2016)
The objective of this research is to illustrate the condition of food security of household level in West Java Province in 2012 by using Susenas data and employing order logistics regression. Moreover, this research tries to explore the factors that affect the household food secure with using 10 independent variables (city dummy, sex dummy, marriage status dummy, age of the household head, the number household, mean years of school of the household head, work dummy, per capita mean expenditure, sanitation dummy, and slum area dummy). In 2002, the number of household in West Java Province with the level of food secure is about 34 percent of total population, however, the number of household with the level of food insecure still high, is about 15 percent of the total population. The output of the regression shows that all the independent variables are statistically significant influence the household food secure.